2013
DOI: 10.1111/jocn.12496
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in women after urinary incontinence and/or pelvic organ prolapse surgery

Abstract: It is important to provide counselling on potential development of postoperative sexual function and the possibility of impairment of sexual function for women undergoing UI and/or POP surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…Currently, the evidence regarding sexual function and rates of dyspareunia following surgical repair of POP varies widely. Some studies have shown a decline in sexual function [10,11], whereas others have shown no change [12,13] or improvement [14][15][16]. In a study by Altman et al [10 they noted an approximately 15 % rate of dyspareunia before surgery, which decreased to 12 % in those with anterior vaginal mesh repairs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the evidence regarding sexual function and rates of dyspareunia following surgical repair of POP varies widely. Some studies have shown a decline in sexual function [10,11], whereas others have shown no change [12,13] or improvement [14][15][16]. In a study by Altman et al [10 they noted an approximately 15 % rate of dyspareunia before surgery, which decreased to 12 % in those with anterior vaginal mesh repairs.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual problems commonly described in women with POP or SUI include disorders of desire, arousal, orgasm and dyspareunia. Disorders in the male partner are also seen, including premature ejaculation and erectile dysfunction [ 5 ]. A community-based survey found no difference between sexual activity and satisfaction compared with women without pelvic floor dysfunction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Other studies have supported the findings of decreased coital pain by vaginal reconstruction. [ 20 21 ] A consensus in the literature seems to be reached among the physical factors of coital incontinence. Incontinence surgery, in patients with coital incontinence, significantly increases the postoperative sexual function scores.…”
Section: Discussionmentioning
confidence: 99%